(untitled) (Proceedings of Southern Federal University. Philology, 2017)
Nikolay F. Alefirenko (Belgorod State National Research University, Belgorod, Russian Federation) The article deals with the problems of idiom production and interpretation, related to the presign forms emergence of information accumulation and storage, contained in cognitive-based derivation of idiom building. The author puts forward the idea that the presign stage of the semiosis process and idiom understanding is a cognitive model that precedes not only the formation of the idiom semantic structure but also its understanding. The fact that the cognitive model of phraseosemiosis is the diagram of discursive meaning embodiment and discourse itself is the form of its indirectly derivative existence stipulates the necessity to show how the cognitive-discoursive mechanisms of idiom building are connected with presign forms of sense accumulation and storage. It is suggested that the elements of the representational code, situated in the cognitive depth of the right semisphere layers of discoursive cognition keep information which has to be coded tby means ofidioms. These very layers form the part of conceptual sphere which is constructed by special cognitive structures which produce idioms. The author calls them discoursive-modus concepts. A mental syntactic model of a discoursive-modus concept which projects the syntagmatic outline of the designator of the idiom-sign is created with the direct involvement of the right semisphere. The character of this designator is determined by the “special syntax” of the inner speech that produces sketchy, fragmentary, abbreviated structures. This conclusion is especially important for the explanation of idiom building because much in the structures of the designator and the designatum of already produced idioms stays implicit, not formally expressed. Since senses of words participating in idiom building are more dynamic and wider than their meanings some illogical mechanisms of their uniting and blending with each other are sometimes revealed. They give the opportunity “to bring to a common denominator” even such associative-metaphorical relations of semes in the structure of the phraseological meaning which are difficult for perception. Key words: presign, representational code, mental model, inner form, sign, gestalt, idiom phraseme. DOI 10.23683/1995-0640-2017-2-50-73